A Descriptive Study to Assess the Knowledge and Practices Among Staff Nurses Regarding Safe Urine Sample Collection in a Selected Hospital in Delhi, India - Anjali Samson; Karishma Gautam; Meena Kumari; Sadiqa; Shalini Singh (International Journal of Community Health Nursing And Practices, 2024)
Urine collection is a quick diagnostic test to assess kidney function. This study investigates the knowledge and practices of nurses regarding urine sample collection, a fundamental aspect of diagnostic procedures. Urine samples are critical for various tests, yet proper collection techniques are essential to ensure accuracy and prevent contamination. The study’s objectives were (a) To assess the level of knowledge among staff nurses regarding safe urine sample collection, and (b) To observe and record the practice among staff nurses regarding safe urine sample collection Method: The research approach selected for this study was quantitative. The sample of 60 staff nurses’ staff from the wards, casualty/emergency, and intensive care unit (ICU) in Hakeem Abdul Hameed Centenary (HAHC) Hospital, New Delhi, was selected by convenient sampling technique. The instruments used for this study were a structured knowledge questionnaire and an observation checklist. The pilot study was conducted to ascertain the feasibility of the study Result and Conclusion: The result of the study revealed that the majority (96.66%) of nursing staff had poor knowledge (70.50%) had poor practice in random urine collection, The mean practice score for random urine sample collection was 8.41 ± 1.93, (76.60%) nursing staff had poor practice in urine culture and sensitivity. The mean practice score was 8.06 ± 2.07. 69.23% had poor practice scores regarding indwelling catheter urine collection. The mean score of practice regarding indwelling catheter urine collection was 7.53 ± 2.01.
Keywords: Knowledge; practice; safe urine sample collection; staff nurses